PVDF / PI (Polyvinylidene Fluoride / Polyimide)-based ultrathin composite electrolyte membrane as well as preparation method and application thereof

Through the preparation of PVDF/PI-based ultra-thin composite electrolyte membrane, the problems of low mechanical properties and lithium ion conductivity of solid electrolytes in lithium-ion batteries are solved, and higher conductivity and mechanical properties are achieved, improving the safety and energy density of the battery.

CN119581645AActive Publication Date: 2025-03-07INST OF ENERGY HEFEI COMPREHENSIVE NAT SCI CENT (ANHUI ENERGY LAB)

Patent Information

Application Number
CN202411862629.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-07
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the mechanical properties and lithium-ion conductivity of solid electrolytes are relatively low, which limits their application.

Method used

Using PVDF/PI-based ultra-thin composite electrolyte membrane, the porous PVDF/PI membrane is prepared, lithium salt is adsorbed and pore-making process is combined with the hot-imprint pore making process, and PVDF/inorganic solid electrolyte components are filled.

Benefits of technology

It significantly improves the mechanical properties and lithium ion conductivity of solid electrolytes, and enhances the safety and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581645A_ABST
    Figure CN119581645A_ABST
Patent Text Reader

Abstract

The invention discloses a PVDF / PI-based ultrathin composite electrolyte membrane and a preparation method and application thereof, and belongs to the field of lithium ion solid electrolytes.The preparation method comprises the steps that a PVDF / PI porous membrane is prepared through a non-solvent phase inversion method, after the membrane is immersed in lithium salt, a large number of regular holes are formed in the surface of the membrane in combination with a hot stamping technology, formula slurry of PVDF / inorganic solid electrolyte is coated, and the PVDF / PI-based ultrathin composite electrolyte membrane is obtained. And obtaining the composite electrolyte membrane. According to the PVDF / PI composite polymer electrolyte membrane prepared by the invention, the mechanical strength of a solid electrolyte membrane is improved to a great extent, the crystallization of PVDF is further destroyed, and the ionic conductivity of the solid electrolyte is improved; the thickness of the electrolyte membrane is controllable, the electrolyte membrane is ultrathin, the preparation process is simple, the cost is relatively low, and the electrolyte membrane has a very good application prospect in all-solid-state lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion solid electrolytes, and in particular relates to a PVDF / PI-based ultra-thin composite electrolyte membrane and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have attracted much attention due to their high specific energy and long cycle life, and have been widely used in portable electronic devices, automobiles and other fields. However, during the use of lithium-ion batteries, organic liquid electrolytes usually have safety issues such as leakage and flammability. Replacing the electrolyte and diaphragm with solid electrolytes is expected to overcome the current safety issues and at the same time be able to match the lithium metal negative electrode to further improve the energy density.

[0003] Among several types of solid electrolytes, polymer electrolyte PVDF has a high dielectric constant, good thermal stability, and high electrochemical stability. However, its room temperature ionic conductivity is low, which limits its further application. At the same time, the film-forming performance of PVDF after compounding with lithium salt is poor, and it is difficult to form a stable film. Polyimide film (PI) has high mechanical strength and is used as a support in solid electrolytes to provide mechanical strength while improving ionic conductivity. In the literature (J. Wan, et al., [J], Nat. Nanotechnol., 2019, 14(7), 705-711), a PI film with array nanopores prepared by track etching was reported. The pores were filled with PEO / LiTFSI solid electrolyte by spin coating to obtain a PI / PEO / LiTFSI composite electrolyte, and the ionic conductivity at 30°C reached 2.3×10 -4 However, this method has low pore-forming efficiency for PI membranes, and since the PI membrane itself is not conductive, the ionic conductivity is not high. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a PVDF / PI-based ultra-thin composite electrolyte membrane and a preparation method and application thereof. The PVDF / PI-based ultra-thin composite electrolyte membrane not only greatly improves the mechanical properties of the solid electrolyte, but also further destroys the crystallization of PVDF and improves the lithium ion conductivity.

[0005] The present invention provides a PVDF / PI-based ultra-thin composite electrolyte membrane, which is obtained by first preparing a porous PVDF / PI porous membrane, adsorbing lithium salt, and then combining a hot embossing pore-forming process to fill PVDF / inorganic solid electrolyte components.

[0006] Preferably, the weight ratio of PVDF / PI is (90-95):(5-10).

[0007] Preferably, the lithium salt is one or more of lithium perchlorate, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonate imide) and lithium bis(fluorosulfonate imide).

[0008] Preferably, the inorganic solid electrolyte is one or more of LATP, LLZO, and LLTO.

[0009] Preferably, the weight ratio of the PVDF to the inorganic solid electrolyte is (10-20): (80-90).

[0010] The present invention also provides a method for preparing a PVDF / PI-based ultra-thin composite electrolyte membrane, comprising the following steps:

[0011] Step 1: Dissolve PVDF / PI powder in dimethylacetamide to form a uniform solution, transfer it to a polytetrafluoroethylene mold to form a film, control the thickness of the film by a scraper, and then quickly transfer it to an ethanol / water solution coagulation bath for 5-30 minutes, and then transfer it to a new ethanol / water solution coagulation bath for 1 day to completely remove the dimethylacetamide, take it out and thoroughly dry it in a vacuum oven at 80°C to obtain a PVDF / PI porous membrane.

[0012] Step 2: Immerse the PVDF / PI porous membrane prepared in step 1 in an acetone solution containing lithium salt for 10-40 minutes, take it out and place it at room temperature until the acetone evaporates to obtain a PVDF / PI membrane containing lithium salt, and hot-press it to obtain a lithium salt / PVDF / PI membrane with holes on the surface.

[0013] Step 3: Grind the inorganic solid electrolyte to obtain a micro-nanoscale slurry, mix and stir with the PVDF glue to obtain an inorganic solid electrolyte / PVDF slurry, apply it on the lithium salt / PVDF / PI membrane with holes on the surface prepared in step 2 by scraping, and dry to remove the solvent to obtain a PVDF / PI-based ultra-thin composite electrolyte membrane.

[0014] Preferably, in step 1, the weight ratio of the coagulation bath ethanol / water solution is (60-70): (30-40), the scraper controls the film thickness to be 10-32 μm, and the obtained PVDF / PI porous film has a thickness of 8-28 μm.

[0015] Preferably, in step 2, the hot stamping temperature is 30-60°C, the pressure is 50-100 MPa, the surface pore depth of the lithium salt / PVDF / PI membrane is 5-15 μm, the spacing between adjacent pores is 5-10 μm, and the shape is one or more of square, triangle, and circle.

[0016] Preferably, in step 3, the drying method is forced air oven drying, the drying temperature is 60-80° C., and the drying time is 24-48 hours.

[0017] The present invention also provides a PVDF / PI-based ultra-thin composite electrolyte membrane and a method for preparing the PVDF / PI-based ultra-thin composite electrolyte membrane and their application in all-solid-state lithium-ion batteries.

[0018] The present invention has the following advantages:

[0019] (1) One of the advantages of the method of the present invention is that adding a small amount of PI to PVDF to form a film can significantly enhance the strength of the porous membrane. At the same time, since PI contains a large number of polar groups, it can interact with the molecular weight of PVDF through hydrogen bonds, thereby inhibiting the crystallization of PVDF and achieving an improvement in ionic conductivity.

[0020] (2) The second advantage of the method of the present invention is that the hot stamping process is beneficial to the penetration of lithium salt into the PVDF / PI porous membrane, and on the other hand, pores are constructed on the surface of the film. After filling with inorganic solid electrolyte, the inorganic solid electrolyte can be anchored. At the same time, the inorganic solid electrolyte can further improve the ionic conductivity and mechanical strength of the entire film. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a schematic diagram of a composite electrolyte membrane prepared in Example 1 of the present invention;

[0022] Figure 2 is the XRD spectrum of the composite electrolyte and PVDF powder prepared in Example 1 of the present invention;

[0023] Figure 3 is the tensile curve of the composite electrolyte prepared in Example 1 / Comparative Example 1 of the present invention;

[0024] Figure 4 This is the impedance spectrum prepared in Example 1 / Comparative Example 1 of the present invention;

[0025] Figure 5 : is the LSV curve of the composite electrolyte prepared in Example 1 / Comparative Example 1 of the present invention;

[0026] Figure 6 It is the constant current charge-discharge cycle curve of the composite electrolyte prepared in Example 1 / Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. However, the following embodiments are limited to explaining the present invention, and the protection scope of the present invention should include the entire contents of the claims, and through the description of the following embodiments, those skilled in the art can fully implement the entire contents of the claims of the present invention.

[0028] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments. If the specific experimental conditions are not specified in the embodiments, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following embodiments, unless otherwise specified, can be obtained through commercial channels.

[0029] Example 1

[0030] (1) Take 90 parts by weight of PVDF and 10 parts by weight of PI powder, dissolve them in dimethylacetamide to form a uniform solution, transfer them to a polytetrafluoroethylene mold to form a film, control the thickness of the film to be 32 μm by a scraper, and then quickly transfer it to a coagulation bath of ethanol / water solution with a weight ratio of 60:40 for 5 minutes, then transfer it to a new ethanol / water solution coagulation bath and place it for 1 day to completely remove the dimethylacetamide, take it out and thoroughly dry it in a vacuum oven at 80°C to obtain a PVDF / PI porous membrane with a thickness of 28 μm.

[0031] (2) Immerse the PVDF / PI porous membrane in an acetone solution containing lithium hexafluorophosphate for 10 minutes, take it out and leave it at room temperature until the acetone evaporates to dryness, and obtain a PVDF / PI membrane containing lithium salt. Set the temperature of hot stamping to 30°C and the pressure to 100MPa. After hot stamping, the surface pores of the lithium salt / PVDF / PI membrane are 5μm deep, the spacing between adjacent pores is 5μm, and the shape is square. A lithium salt / PVDF / PI membrane with pores on the surface is obtained.

[0032] (3) The inorganic solid electrolyte LATP was subjected to high-energy ball milling to obtain a micro-nanoscale slurry, which was mixed with PVDF glue to obtain an inorganic solid electrolyte / PVDF slurry, and the weight ratio of PVDF to inorganic solid electrolyte was 20:80. It was coated on the above-mentioned lithium salt / PVDF / PI membrane with holes by a doctor blade method, and dried in a forced air oven at a drying temperature of 60°C for 48 hours to obtain a PVDF / PI-based ultra-thin composite electrolyte membrane with a thickness of 30 μm.

[0033] Example 2

[0034] (1) Take 95 parts by weight of PVDF and 5 parts by weight of PI powder, dissolve them in dimethylacetamide to form a uniform solution, transfer them to a polytetrafluoroethylene mold to form a film, control the thickness of the film to be 10 μm by a scraper, and then quickly transfer it to a coagulation bath of ethanol / water solution with a weight ratio of 60:40 for 30 minutes, then transfer it to a new ethanol / water solution coagulation bath and place it for 1 day to completely remove the dimethylacetamide, take it out and thoroughly dry it in a vacuum oven at 80°C to obtain a PVDF / PI porous membrane with a thickness of 8 μm.

[0035] (2) Immerse the PVDF / PI porous membrane in an acetone solution containing lithium perchlorate for 40 minutes, take it out and leave it at room temperature until the acetone evaporates to dryness, and obtain a PVDF / PI membrane containing lithium salt. Set the temperature of hot stamping to 30°C and the pressure to 50MPa. After hot stamping, the surface pores of the lithium salt / PVDF / PI membrane are 5μm deep, the spacing between adjacent pores is 5μm, and the shape is circular. A lithium salt / PVDF / PI membrane with pores on the surface is obtained.

[0036] (3) The inorganic solid electrolyte LLZO was subjected to high-energy ball milling to obtain a micro-nanoscale slurry, which was mixed with PVDF glue to obtain an inorganic solid electrolyte / PVDF slurry, and the weight ratio of PVDF to inorganic solid electrolyte was 20:80. It was coated on the above-mentioned lithium salt / PVDF / PI membrane with holes by a doctor blade method, and dried in a forced air oven at a drying temperature of 80°C for a drying time of 48 hours to obtain a PVDF / PI-based ultra-thin composite electrolyte membrane with a thickness of 10 μm.

[0037] The tensile strength reaches 3.5MPa at room temperature, the tensile elongation is 300%, the ionic conductivity at 30°C is 0.35mS / cm, and the electrochemical window tested at 45°C can reach 4.9V.

[0038] Example 3

[0039] (1) Take 92 parts by weight of PVDF and 8 parts by weight of PI powder, dissolve them in dimethylacetamide to form a uniform solution, transfer them to a polytetrafluoroethylene mold to form a film, control the thickness of the film to be 15 μm by a scraper, and then quickly transfer it to a coagulation bath of ethanol / water solution with a weight ratio of 65:35 for 30 minutes, then transfer it to a new ethanol / water solution coagulation bath and place it for 1 day to completely remove the dimethylacetamide, take it out and thoroughly dry it in a vacuum oven at 80°C to obtain a PVDF / PI porous membrane with a thickness of 12 μm.

[0040] (2) Immerse the PVDF / PI porous membrane in an acetone solution containing lithium bis(fluorosulfonate)imide for 25 minutes, take it out and leave it at room temperature until the acetone evaporates to dryness, and obtain a PVDF / PI membrane containing lithium salt. Set the temperature of hot stamping to 35°C and the pressure to 50MPa. After hot stamping, the surface pores of the lithium salt / PVDF / PI membrane are 5μm deep, the spacing between adjacent pores is 7μm, and the shape is square. A lithium salt / PVDF / PI membrane with pores on the surface is obtained.

[0041] (3) The inorganic solid electrolyte LLTO was subjected to high-energy ball milling to obtain a micro-nanoscale slurry, which was mixed with PVDF glue to obtain an inorganic solid electrolyte / PVDF slurry, and the weight ratio of PVDF to inorganic solid electrolyte was 15:85. It was coated on the above-mentioned lithium salt / PVDF / PI membrane with holes by a doctor blade method, and dried in a forced air oven at a drying temperature of 80°C for a drying time of 36 hours to obtain a PVDF / PI-based ultra-thin composite electrolyte membrane with a thickness of 15 μm.

[0042] The tensile strength reaches 6.5MPa at room temperature, the tensile elongation is 210%, the ionic conductivity at 30°C is 1.1mS / cm, and the electrochemical window tested at 45°C can reach 5.35V.

[0043] Example 4

[0044] (1) Take 90 parts by weight of PVDF and 10 parts by weight of PI powder, dissolve them in dimethylacetamide to form a uniform solution, transfer them to a polytetrafluoroethylene mold to form a film, control the thickness of the film to be 15 μm by a scraper, and then quickly transfer it to a coagulation bath of ethanol / water solution with a weight ratio of 70:30 for 15 minutes, then transfer it to a new ethanol / water solution coagulation bath and place it for 1 day to completely remove the dimethylacetamide, take it out and thoroughly dry it in a vacuum oven at 80°C to obtain a PVDF / PI porous membrane with a thickness of 13 μm.

[0045] (2) Immerse the PVDF / PI porous membrane in an acetone solution containing lithium bis(fluorosulfonate)imide for 10 minutes, take it out and leave it at room temperature until the acetone evaporates to dryness, and obtain a PVDF / PI membrane containing lithium salt. Set the temperature of hot stamping to 50°C and the pressure to 60MPa. After hot stamping, the surface pores of the lithium salt / PVDF / PI membrane are 5μm deep, the spacing between adjacent pores is 5μm, and the shape is triangular. A lithium salt / PVDF / PI membrane with pores on the surface is obtained.

[0046] (3) The inorganic solid electrolyte LATP was subjected to high-energy ball milling to obtain a micro-nanoscale slurry, which was mixed with PVDF glue to obtain an inorganic solid electrolyte / PVDF slurry, and the weight ratio of PVDF to inorganic solid electrolyte was 10:90. It was coated on the above-mentioned lithium salt / PVDF / PI membrane with holes by a doctor blade method, and dried in a forced air oven at a drying temperature of 80°C for a drying time of 48 hours to obtain a PVDF / PI-based ultra-thin composite electrolyte membrane with a thickness of 17 μm.

[0047] The tensile strength reaches 7.5MPa at room temperature, the tensile elongation is 220%, the ionic conductivity at 30°C is 0.75mS / cm, and the electrochemical window tested at 45°C can reach 5.75V.

[0048] Comparative Example 1

[0049] (1) Take 100 parts by weight of PVDF, dissolve it in dimethylacetamide to form a uniform solution, transfer it to a polytetrafluoroethylene mold to form a film, control the thickness of the film to be 32 μm by a scraper, and then quickly transfer it to a coagulation bath of ethanol / water solution with a weight ratio of 60:40 for 5 minutes, then transfer it to a new ethanol / water solution coagulation bath and place it for 1 day to completely remove the dimethylacetamide, take it out and thoroughly dry it in a vacuum oven at 80°C to obtain a PVDF porous membrane with a thickness of 28 μm.

[0050] (2) Immerse the PVDF porous membrane in an acetone solution containing lithium hexafluorophosphate for 10 minutes, take it out and leave it at room temperature until the acetone evaporates to dryness, and obtain a PVDF membrane containing lithium salt. Set the temperature of hot stamping to 30°C and the pressure to 100MPa. After hot stamping, the surface pores of the lithium salt / PVDF membrane are 5μm deep, the spacing between adjacent pores is 5μm, and the shape is square. A lithium salt / PVDF / PI membrane with pores on the surface is obtained.

[0051] (3) The inorganic solid electrolyte LATP was subjected to high-energy ball milling to obtain a micro-nanoscale slurry, which was mixed with PVDF glue to obtain an inorganic solid electrolyte / PVDF slurry, and the weight ratio of PVDF to inorganic solid electrolyte was 20:80. It was coated on the above-mentioned lithium salt / PVDF membrane with holes by a doctor blade method, and dried in a forced air oven at a drying temperature of 60°C for 48 hours to obtain a PVDF-based ultra-thin composite electrolyte membrane with a thickness of 30 μm.

[0052] pass Figure 3 It can be seen that the tensile strength at room temperature is only 0.7MPa, and the tensile elongation is 80%. Figure 4 It can be seen that the ionic conductivity at 30°C is 0.05 mS / cm. Figure 5 It can be seen that the electrochemical window tested at 45°C is only 3.8V. Figure 6 It can be seen that the voltage polarization is very large, and a micro short circuit occurs around 130 hours. This shows that when there is no PI in the system, on the one hand, the structure cannot provide sufficient strength, and on the other hand, the crystallinity of PVDF cannot be reduced, resulting in low ionic conductivity.

[0053] Comparative Example 2

[0054] (1) Take 90 parts by weight of PVDF and 10 parts by weight of PI powder, dissolve them in dimethylacetamide to form a uniform solution, transfer them to a polytetrafluoroethylene mold to form a film, control the thickness of the film to be 32 μm by a scraper, and then quickly transfer it to a coagulation bath of ethanol / water solution with a weight ratio of 60:40 for 5 minutes, then transfer it to a new ethanol / water solution coagulation bath and place it for 1 day to completely remove the dimethylacetamide, take it out and thoroughly dry it in a vacuum oven at 80°C to obtain a PVDF / PI porous membrane with a thickness of 28 μm.

[0055] (2) The PVDF / PI porous membrane was immersed in an acetone solution containing lithium hexafluorophosphate for 10 minutes, and then the membrane was taken out and left at room temperature to allow the acetone to evaporate to dryness, thereby obtaining a PVDF / PI membrane containing lithium salt.

[0056] (3) The inorganic solid electrolyte LATP was subjected to high-energy ball milling to obtain a micro-nanoscale slurry, which was mixed with PVDF glue to obtain an inorganic solid electrolyte / PVDF slurry, and the weight ratio of PVDF to inorganic solid electrolyte was 20:80. It was coated on the above lithium salt / PVDF / PI membrane by a doctor blade method, and dried in a forced air oven at a drying temperature of 60°C for 48 hours to obtain a PVDF / PI-based ultra-thin composite electrolyte membrane with a thickness of 30 μm.

[0057] The tensile strength at room temperature is only 2.5MPa, the tensile elongation is 150%, the ionic conductivity at 30°C is 0.15mS / cm, and the electrochemical window tested at 45°C is only 4.5V. This shows that without the hot stamping process, the inorganic solid electrolyte cannot be effectively filled into the PVDF / PI base film, resulting in a decrease in various performances.

[0058] Comparative Example 3

[0059] (1) Take 90 parts by weight of PVDF and 10 parts by weight of PI powder, dissolve them in dimethylacetamide to form a uniform solution, transfer them to a polytetrafluoroethylene mold to form a film, control the thickness of the film to be 32 μm by a scraper, and then quickly transfer it to a coagulation bath of ethanol / water solution with a weight ratio of 60:40 for 5 minutes, then transfer it to a new ethanol / water solution coagulation bath and place it for 1 day to completely remove the dimethylacetamide, take it out and thoroughly dry it in a vacuum oven at 80°C to obtain a PVDF / PI porous membrane with a thickness of 28 μm.

[0060] (2) Immerse the PVDF / PI porous membrane in an acetone solution containing lithium hexafluorophosphate for 10 minutes, take it out and leave it at room temperature until the acetone evaporates to dryness, and obtain a PVDF / PI membrane containing lithium salt. Set the temperature of hot stamping to 30°C and the pressure to 100MPa. After hot stamping, the surface pores of the lithium salt / PVDF / PI membrane are 5μm deep, the spacing between adjacent pores is 5μm, and the shape is square. A lithium salt / PVDF / PI membrane with pores on the surface is obtained.

[0061] (3) The PVDF glue was coated on the lithium salt / PVDF / PI membrane with holes by blade coating, and dried in a forced air oven at a temperature of 60°C for 48 h to obtain a PVDF / PI-based ultra-thin composite electrolyte membrane with a thickness of 30 μm.

[0062] The tensile strength at room temperature is only 3.0 MPa, the tensile elongation is 190%, the ionic conductivity at 30°C is 0.15 mS / cm, and the electrochemical window tested at 45°C is 4.2 V. This shows that without the inorganic solid electrolyte composite, the crystallinity of PVDF is difficult to reduce, resulting in lower ionic conductivity.

[0063] Experimental tests and results

[0064] like Figure 1 As shown, left Figure 1 (a) is a cross-sectional view of the PVDF / PI-based ultra-thin composite electrolyte membrane. Figure 1 (b) is a top view of the PVDF / PI-based ultra-thin composite electrolyte membrane.

[0065] like Figure 2 As shown, XRD test shows that the crystallinity of PVDF is significantly reduced, indicating that the addition of PI and inorganic solid electrolyte can effectively inhibit the crystallization of PVDF.

[0066] like Figure 3 As shown, the mechanical properties test shows that the tensile strength of the composite solid electrolyte membrane reaches 5.5 MPa at room temperature, and the tensile elongation is 250%, indicating that the solid electrolyte has good mechanical properties.

[0067] like Figure 4 As shown in the figure, the composite electrolyte membrane was cut into discs with a diameter of 10 μm and tested with a button cell (SS / SSE / SS) composed of two stainless steel sheets. The AC impedance spectrum of the steel sheet symmetrical cell was tested using an electrochemical workstation with a test frequency range of 0.01-10 6 Hz, the ionic conductivity of the solid electrolyte at 30°C is 0.16 mS / cm.

[0068] like Figure 5As shown, the composite electrolyte membrane was assembled into a half-cell (SS / SSE / Li) consisting of a steel sheet and a lithium sheet, and a linear sweep voltammetry test was performed using an electrochemical workstation. The test voltage range was 2.5-6V, the scan rate was 1mV / s, and the test was performed at 45°C. The results show that the electrochemical window of the composite electrolyte membrane can reach 5.4V, indicating that the composite electrolyte membrane can effectively prevent the interfacial side reactions between the electrolyte and the lithium sheet, and obtain a wide and temperature-controlled electrochemical window.

[0069] As shown in Figure 6, in the lithium battery cycle stability test, the composite electrolyte membrane was blocked into a lithium symmetric battery (Li / SSE / Li), and the battery was tested using a blue power test system at 60°C for 400 hours of stable cycling. The results showed that the composite solid electrolyte membrane not only improved the cycle stability, but also inhibited the growth of lithium dendrites.

[0070] The above embodiments are merely descriptions of preferred implementations of the present invention, and are not intended to limit the concept and protection scope of the present invention. It should be noted that, for those skilled in the art, under the premise of the present invention, the present invention can also be improved and perfected, and these improvements and perfections also fall within the protection scope of the claims of the present invention.

Claims

1. A PVDF / PI-based ultra-thin composite electrolyte membrane, characterized in that: The porous PVDF / PI porous membrane is prepared first, and after the lithium salt is adsorbed, the PVDF / inorganic solid electrolyte components are filled in combination with a hot embossing pore-making process.

2. A PVDF / PI-based ultra-thin composite electrolyte membrane according to claim 1, characterized in that: The weight ratio of the PVDF / PI is (90-95):(5-10).

3. A PVDF / PI-based ultra-thin composite electrolyte membrane according to claim 1, characterized in that: The lithium salt is one or more of lithium perchlorate, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonic acid)imide, and lithium bis(fluorosulfonic acid)imide.

4. The PVDF / PI-based ultra-thin composite electrolyte membrane according to claim 1, characterized in that: The inorganic solid electrolyte is one or more of LATP, LLZO and LLTO.

5. The PVDF / PI-based ultra-thin composite electrolyte membrane according to claim 1, characterized in that: The weight ratio of the PVDF to the inorganic solid electrolyte is (10-20): (80-90).

6. A method for preparing a PVDF / PI-based ultrathin composite electrolyte membrane, characterized in that: The following steps are involved: Step 1, dissolving PVDF / PI powder in dimethylacetamide to form a uniform solution, transferring it to a polytetrafluoroethylene mold to form a film, controlling the thickness of the film by a scraper, and then quickly transferring it to an ethanol / water solution coagulation bath for 5-30 minutes, and then transferring it to a new ethanol / water solution coagulation bath for 1 day to completely remove the dimethylacetamide, taking it out and thoroughly drying it in a vacuum oven at 80°C to obtain a PVDF / PI porous membrane; Step 2, immersing the PVDF / PI porous membrane prepared in step 1 into an acetone solution containing lithium salt for 10-40 minutes, taking it out and placing it at room temperature until the acetone evaporates to dryness, thereby obtaining a PVDF / PI membrane containing lithium salt, and hot-pressing it to obtain a lithium salt / PVDF / PI membrane with holes on the surface; Step 3: Grind the inorganic solid electrolyte to obtain a micro-nanoscale slurry, mix and stir with the PVDF glue to obtain an inorganic solid electrolyte / PVDF slurry, apply it on the lithium salt / PVDF / PI membrane with holes on the surface prepared in step 2 by scraping, and dry to remove the solvent to obtain a PVDF / PI-based ultra-thin composite electrolyte membrane.

7. The method for preparing a PVDF / PI-based ultra-thin composite electrolyte membrane according to claim 6, characterized in that: In step 1, the weight ratio of the coagulation bath ethanol / water solution is (60-70): (30-40), the scraper controls the film thickness to be 10-32 μm, and the obtained PVDF / PI porous film has a thickness of 8-28 μm.

8. The method for preparing a PVDF / PI-based ultra-thin composite electrolyte membrane according to claim 6, characterized in that: In step 2, the temperature of the hot stamping is 30-60°C, the pressure is 50-100 MPa, the surface hole depth of the lithium salt / PVDF / PI membrane is 5-15 μm, the spacing between adjacent holes is 5-10 μm, and the shape is one or more of square, triangle, and circle.

9. Application of any one of the PVDF / PI-based ultra-thin composite electrolyte membranes of claims 1 to 5 or the method for preparing any one of the PVDF / PI-based ultra-thin composite electrolyte membranes of claims 6 to 8 in all-solid-state lithium-ion batteries.

Citation Information

Patent Citations

  • Composite solid-state electrolyte membrane, preparation method thereof and solid-state lithium battery

    CN115663278A

  • Fiber network self-reinforced composite polymer solid electrolyte membrane and preparation method thereof

    CN118117161A

  • Large-dimension, flexible, ultrathin high-conductivity polymer-based composite solid-state electrolyte membrane

    US20230035720A1

Cited By

  • In-situ graft-modified composite solid electrolyte membrane and method for preparing the same

    CN122511972A